2017
DOI: 10.15171/ijhpm.2017.73
|View full text |Cite
|
Sign up to set email alerts
|

Informal Patient Payments and Bought and Brought Goods in the Western Balkans – A Scoping Review

Abstract: Introduction: Informal patient payments for healthcare are common in the Western Balkans, negatively affecting public health and healthcare. Aim: To identify literature from the Western Balkans on what is known about informal patient payments and bought and brought goods, to examine their effects on healthcare and to determine what actions can be taken to tackle these payments. Methods: After conducting a scoping review that involved searching websites and databases and filtering with eligibility criteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It has been stated that informal patient payment is an apparent sociocultural phenomenon that develops by passing the time [72,73]. Lost trust, corruption, and value culture, public/ patient awareness and community participation were the common aspects of this complicate social phenomenon, which was proved in national and international studies [17,18,34,37,41] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that informal patient payment is an apparent sociocultural phenomenon that develops by passing the time [72,73]. Lost trust, corruption, and value culture, public/ patient awareness and community participation were the common aspects of this complicate social phenomenon, which was proved in national and international studies [17,18,34,37,41] .…”
Section: Discussionmentioning
confidence: 99%
“…It posits that users' primary motivation for making IP is the prospect that they will receive a quicker and a higher quality of care that is more personalized and convenient and has shorter wait times and that they will have access to more advanced or specialized care and services [2,[45][46][47]. As an illustration, Riewpaiboon and colleagues detailed how a Thai woman made informal payments to an obstetrician to get better services during her pregnancy [48], while several other studies confirmed that IP resulted in a better relationship between users and healthcare personnel and consequently in higher levels of satisfaction for users [4,5,49,50]. On the other hand, IP eases the inefficiencies of administering public healthcare in a situation where healthcare workers believe that they are not being paid adequately and so have the expectation of IP, while concurrently, users expect to pay out-of-pocket to underpaid professionals for more or better-quality service [15,41,51,52].…”
Section: Methodsmentioning
confidence: 99%
“…In other words, they may feel dissatisfaction that they have to make IP to receive higher quality and faster services since they believe that such quality and speed should be available without additional "grease the wheels" IP. Second, users could make "grease the wheels" IP to get better and faster services, but after receiving services, they may be unsatisfied with the quality and speed of services which they received [5]. Hence, they may question whether such quality and speed justify making "grease the wheels" payments.…”
Section: Satisfaction With Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of the sample had a negative attitude towards informal payments but about 27% of respondents had a positive attitude towards the practice. It also reported that Albania, one of the poorest countries in Europe, provides most health care services free of charge, but still more informal payments to medical personnel are common [15]. Its studies suggested that 60-70% of Albanian citizens made informal payments to hospital doctors in order to receive services.…”
Section: Introductionmentioning
confidence: 99%